Assessment of Outcome in Hypospadias Surgery – A Review - Springer, Alexander (Frontiers in Pediatrics, 2014)
Hypospadias is a challenging field of urogenital reconstructive surgery with different techniques being currently used. Modern surgery claims that it is possible to create a functionally and cosmetically normal penis. Continuous reevaluation and assessment of outcome may have a major impact on future clinical practice. Assessment of outcome includes: complication rate, cosmetic appearance of the penis, functional outcome (micturition, sexuality) and psychological factors such as quality of life and psychosexual life. This article briefly reviews current strategies of outcome assessment and outlines that in the future long-term assessment should be designed in web-based prospective studies multicenter studies. Somehow in the future we will be able to give an accurate estimation of the long-term consequences of being born with hypospadias.